2020
DOI: 10.1021/acs.jchemed.0c00353
|View full text |Cite
|
Sign up to set email alerts
|

Epistemological Profile of Chemical Bonding: Evaluation of Knowledge Construction in High School

Abstract: This work aims to evaluate the evolution of chemical bonding concepts of high school students at public schools in southern Brazil. For this, we built the epistemological profile of each student who took part in a teaching-learning sequence (TLS) about this topic, based on the foundations of Bachelard's theory. Following the principles of the qualitative survey, we applied questionnaires to monitor the students' ideas. The results revealed that the construction of knowledge took place by overcoming epistemolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…Evidence is abundant that although bonding is central to the chemistry curriculum and covered multiple times through the chemistry major, it is an area in which students often have misunderstandings or have difficulty applying the appropriate bonding models. For example, at the high school and introductory/general chemistry level, research has investigated student misunderstandings of the energetics of bond making/breaking and has identified alternative conceptions associated with covalent and ionic bonding. In subdisciplinary areas, researchers have documented students’ understanding of polarity, molecular orbitals, and resonance in organic chemistry; coordination number for transition metal complexes in inorganic chemistry; and quantum chemical models in physical chemistry. Interestingly, researchers have found that, even after exposure to more sophisticated bonding models, students often rely on simpler, more realistic models in their explanations. ,, Thus, bonding seemed an appropriate content area to target since it is both a central theme underlying the chemistry curriculum and an area that research has shown to illustrate a diverse set of ideas among students at all levels.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence is abundant that although bonding is central to the chemistry curriculum and covered multiple times through the chemistry major, it is an area in which students often have misunderstandings or have difficulty applying the appropriate bonding models. For example, at the high school and introductory/general chemistry level, research has investigated student misunderstandings of the energetics of bond making/breaking and has identified alternative conceptions associated with covalent and ionic bonding. In subdisciplinary areas, researchers have documented students’ understanding of polarity, molecular orbitals, and resonance in organic chemistry; coordination number for transition metal complexes in inorganic chemistry; and quantum chemical models in physical chemistry. Interestingly, researchers have found that, even after exposure to more sophisticated bonding models, students often rely on simpler, more realistic models in their explanations. ,, Thus, bonding seemed an appropriate content area to target since it is both a central theme underlying the chemistry curriculum and an area that research has shown to illustrate a diverse set of ideas among students at all levels.…”
Section: Introductionmentioning
confidence: 99%
“…Although Bachelard does not establish a pedagogical framework to support the construction of the scientific mind, the philosopher points out that phenomenological studies which start from images that are considered easy and familiar can encourage the individual to propose original and unusual hypotheses, and this helps promote one's evolution from the concrete state. In this context, the main objective here is to discuss how the epistemology of Bachelard can help understand the variables involved in the student's arguments, as well as the form, the why and how the participants can develop a scientific mind inside the Chemistry Club, through the application of a qualitative analytical technique (Chin and Osborne, 2008;Merriam and Grenier, 2019;Pazinato et al, 2021).…”
Section: Data Collection Instrumentsmentioning
confidence: 99%
“…Furthermore, the answers provided individually by the participants in the initial and final questionnaires, the reactions of the participants during the club meetings, the development of arguments, the employment of scientific terms, the construction of hypotheses, and the progress of the scientific state of the participants were all observed and analysed by the two chemists, one man and one woman, researchers of science communication at the São Carlos Institute of Chemistry (IQSC-USP). This analysis was conducted based on studies previously reported in the literature (Pazinato et al, 2021). Figure 2 provides a simplified illustration of a data collection step.…”
Section: Data Collection Instrumentsmentioning
confidence: 99%
“…Chemical bonding on the subject of organic chemistry is one of the basic concept that must be understood by students [1]. Chemical bonds allow for a compound to be formed a compound can be formed, including the characteristics of every compound's molecules [2].…”
Section: Introductionmentioning
confidence: 99%